Comparative analysis of different grades of Tieguanyin oolong tea based on metabolomics and sensory evaluation. (15th January 2023) - Zeng, Lin; Fu, Yan-Qing; Liu, Yu-Yi; Huang, Jin-Shui; Chen, Jian-Xin; Yin, Jun-Feng; Jin, Shan; Sun, Wei-Jiang; Xu, Yong-Quan
Abstract: To develop objective methods of oolong tea grading for importers and customs, metabolomics and sensory evaluation were applied to screen the characteristic compounds associated with Tieguanyin (TGY) tea grades T, 1, 2, and 3, and types (fresh scent flavor and high fragrance). With decreasing TGY grade/quality, the astringency and content of most flavonoid glycosides increased (especially catechin and epicatechin). The floral aroma of fresh scent flavor TGY decreased, and the roasted aroma of high-fragrance TGY increased with decreasing TGY grade. Five non-volatile compounds (epicatechin gallate, quercetin-3- O -galactoside, quercetin-3- O -rutinoside, epicatechin, and gallocatechin) and five volatile compounds (benzyl benzoate, β -phenylethyl acetate, 6-methyl-5-hepten-2-one, heptanal, and ( E )-2-hexenal) were identified, which could readily distinguish different grades of fresh scent flavor and high fragrance TGY by quantitative chemical analysis. Lower grades of TGY had inferior flavor, but higher antioxidant capacity. Highlights: Sensory evaluation and metabolomics were combined for Tieguanyin grade analysis. As Tieguanyin grades decreased, the astringency increased. Ten compounds were identified as the key metabolites for Tieguanyin grades. Low-grade tea has higher antioxidant capacity due to more polyphenols.